Intermediate layer contribution in placental membrane allografts. (12th July 2020) - Roy, Annelise; Griffiths, Sarah
Abstract: Placental membrane (PM) allografts are commonly used to treat chronic wounds. Native PM is composed of an amnion, chorion, and intermediate layer (IL) that contain matrix structures and regulatory components beneficial in wound healing. Historically, commercially available allografts were composed of only one or two layers of the PM. To maximize the conserved material in PM allografts, a dehydrated complete human placental membrane (dCHPM) allograft processed using the Clearify™ process was developed. Histological and proteomic characterization comparing dCHPM allografts with native PM demonstrated that the majority of matrix structures and regulatory proteins are retained in dCHPM allografts through processing. To evaluate the importance of maintaining the entire intact PM and the contribution of the IL, the structural and proteomic makeup of the IL was compared with that of dCHPM allografts. This is the first known characterization of regulatory proteins in the IL. Results demonstrate that the IL contains over 900 regulatory and signaling components, including chemokines, growth factors, interleukins, and protease inhibitors. These components are key regulators of angiogenesis, neurogenesis, osteogenesis, inflammation, tissue remodeling, and host defense. The results show that the proteomic composition of the IL is consistent with that of the entire dCHPM allograft. Although further investigation is required to fully understand the contribution of the IL in PM allografts, these results demonstrate that the IL contains structural and regulatory proteins that can enhance the barrier and wound healing properties of PM allografts.